Does Profitability Moderate Firm Financial Performance towards Firm Value in the Food and Beverage-Based Sector? - Widyakto, Adhi; Nurafni Octavia, Ayu; Susanto, Susanto; Indi, Rifka; Ghafar Ismail, Abdul (Economics and Business Solutions Journal, 2025)
This study was conducted to determine how to increase company value based on Capital, Debt Policy, and Sales Growth with Profitability as a Moderating variable in Food and Beverage Companies listed on the IDX for the 2021-2023 period. The sampling method used is Purposive Sampling. The sample is 11 companies listed on the IDX. The data processing method used is the Quantitative Method with the help of Smart PLS software version 4.0. The results of this study indicate that the Current Ratio has a positive and significant effect on Price Book Value. Debt-to-Equity Ratio has a positive and significant effect on Price-to-Book Value. Sales Growth has a positive and significant effect on Price Book Value. Return on Assets can moderate the Current Ratio on Price Book Value. Return on Assets moderates the Debt to Equity Ratio on Price to Book Value. Return On Assets moderates Sales Growth on Price Book Value.